Pengaruh Profitability, Pbv, Firm Size Dan Dividen Terhadap Abnormal Return - Chintia Triana, Hendro Lukman (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this study aims to determine and analyze the influence of profitability, price to book value, firm size, and dividend on abnormal return. The subjects of this research are the mining sectors listed on the Indonesia Stock Exchange for the year 2015-2019. The Sampling technique use was purposive sampling and the valid data was 20 companies. Data processing techniques used is multiple regression analysis what helped by SPSS version 22 program (Statistical Product and Service Solution) and Microsoft Excel 2010. The result of this study indicate that independent profitability, firm size, and dividen have no significant effect on abnormal return. While price to book value have a significant negative effect on abnormal return. The implication of this study is the need to increase profitability, and dividend so that will minimize abnormal return.